Daya Toksitas Bacillus Thuringiensis Serovar Israelensis Terhadap Larva Bactrocera Papayae - Samsuddin Samsuddin; Arman Saokani; Dwi Kartika Risfianty; Pahmi Husain; Baiq Naili Dewi Atika; Khaerul Ihwan (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2022)
Bacillus thuringiensis is one of the bacterial species that produces a bioinsecticide known as Bacillus thuringiensis toxin. The purpose of this study was to determine the toxicity of Bacillus thuringiensis var israelensis to Bactocera papayae larvae. Larvicidal activity was calculated based on the percentage of total larval mortality after exposure to Bacillus thuringsiensis var israelensis spores for 24, 36, 48 hours. The results showed that the mortality of Bactocera papayae larvae instar III-IV ranged from 0-30% which was challenged with 106-108 spores/ml. Bacillus thuringiensis var israelensis exposed to Culex sp mosquitoes can kill up to 100% at a concentration of 104 spores/ml.